Effectiveness Of Using Story Map Technique On Level Of Comprehension Skill Among School Going Students - Lenka, Durgesh Nandini; Sahoo, Ranjita; Sahoo, Smrutirekha; Rout, Sasmita; Mishra, Sasmita (Journal of Neonatal Surgery, 2025)
Material and Method-A Nearly exploratory study utilizing a Pre test Post test research methodology was carried out with sixty enrolled students to look into the impact of the Story Map Technique on comprehension ability lebel in a particular school in Odisha.samples that fit the requirements for inclusion are devided into two groups-Thirty for experimental group and thirty for control group.A standardized narrative map questionnaire and a self-structured sociodemographic performance instrument were utilized to gather sociodemographic data and gauge understanding ability. Result & Conclusion- The descriptive & inferential statics used for this study resulted disparity between the comprehension skill levels before and after the test after giving story map technique as evidenced by t Test value at p=0.000 which is extremely significant.it is implied that the comprehension skills varied considerably l level after giving story map technique to the school going students.